New data on the morphology and taxonomy of three species of Rhabdochona (Nematoda:Rhabdochonidae) parasitizing fishes in India - Moravec, Frantisek; Scholz, Tomás; Ash, Anirban; Kar, Pradip Kumar (Folia parasitologica, 2010)
Specimens of three little-known species of Rhabdochona (Nematoda: Rhabdochonidae) were collected during occasional examinations of some freshwater fishes in India: R. (Rhabdochona) hellichi turkestanica (Skryabin, 1917) in Schizothorax sp. (Cyprinidae, Cypriniformes) from the Lodhomakhola and Rangit Rivers, West Bengal and Sikkim, respectively; R. (R.) hospeti Thapar, 1950 in Tor sp. (Cyprinidae) from the Rangit River; and R. (Globochona) mazeedi Prasad et Sahay, 1965 in Clupisoma garua (Hamilton) (Schilbeidae, Siluriformes) from the Farakka Dam Lake, West Bengal. Their detailed light and electron microscopical studies revealed some taxonomically important, previously not observed features and made possible their redescription. Fourth-stage larvae of R. hospeti are described for the first time. Rhabdochona hellichi turkestanica (syns. R. denudata filamentosa Bykhovskaya-Pavlovskaya, 1936, R. kashmirensis Thapar, 1950, R. schizothoracis Siddiqi et Khattak, 1984) is proposed as a subspecies, differing from the nominotypical subspecies R. hellichi hellichi (Srámek, 1901) mainly in the shape of the distal end of the left spicule, molecular data and geographical distribution. Rhabdochona moraveci Katoch et Kalia, 1991 (a homonym to R. moraveci Duggal et Kaur, 1987) is renamed R. indica nom. n. The following six species are considered new junior synonyms of R. hospeti: Comephronema [sic] mackiewiczi Malhotra et Rautela, 1984, Rhabdochona moraveci Duggal et Kaur, 1987, R. bifidum Kakar et Bilqees, 2007, R. uvaginus Kakar et Bilqees, 2007, R. bolani Kakar, Bilqees et Ahmad, 2008 and R. cephalodiverticula Kakar, Bilqees et Ahmad, 2008. Rhabdochona edentati Paul et Majumdar, 1994 is considered a species incertae sedis.
Keywords: Spiruroidea; Animals; India; nemoci ryb; Spirurida Infections; infekce hlísticemi řádu Spirurida; Female; zvířata; mužské pohlaví; Fish Diseases; Fishes; Male; Indie; ženské pohlaví; ryby